Representasi Objek Wisata Jawa Tengah dalam Naskah Literasi Digital - Mulasih Mulasih; Eko Sri Israhayu; Akhmad Fauzan; Brenda Dara Sekar Ayuningtyas (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Tourism literature has increasingly been recognized as a strategic medium for promoting local wisdom–based tourism. In this regard, the present study aims to investigate the function of literary tourism texts published by the Balai Bahasa Jawa Tengah in representing and promoting tourism destinations in Central Java. Employing a qualitative approach with a literature study method, five tourism-themed texts were analyzed using Huberman and Miles’ analytical framework. The findings indicate that Festival Layang-Layang di Pantai Ketawang, Gerabah Mak Nah, Ingin Melihat Dieng Culture Festival, Berkunjung di Desa Klipoh, and Jangan Macam-macam dengan Keluarga Mosi represent tourism destinations and activities in explicit, semi-explicit, and symbolic forms. Furthermore, the texts play a strategic role in tourism promotion by (1) emphasizing the uniqueness of destinations, (2) constructing family-oriented attractions, and (3) embedding the values of conservation, education, collaboration, and digitalization. In conclusion, literary tourism, positioned within the scope of digital literacy, not only promotes tourism through narrative representations of cultural distinctiveness and added value, but also enhances its relevance and fosters stronger emotional engagement among childrens audiences.